Using new social media and Web 2.0 technologies in business school teaching and learning - THOMAS, Michael (Institutional Knowledge at Singapore Management University, 2012)
The purpose of this paper is to examine the role of social and digital media in the business school and particularly to examine how such innovative technological processes can be leveraged to enhance teaching instruction and enrich learning about practice and research. Taking a broad perspective on the range of social and digital media approaches, the paper discusses a series of extant models of technology-based learning and conjectures about how they can be used creatively and meaningfully in business school teaching. Despite the pioneering efforts of the Open University in modelling distance and blended learning, adoption of such models in the business school context has been quite slow. These technologies are used more frequently as support mechanisms for “face-to-face” learning in order to enrich the quality of conventional professorial instructional approaches. In many business schools “face-to-face” learning is perceived to be of much higher quality than on-line learning approaches. The paper notes the resistance to the adoption of new technology both by business school professors and deans. In the case of professors, there is inertia to change and a staunch defence of classic forms of “face-to-face” instruction. In the case of deans, few have sufficient courage or time (given the short average tenure of deans) to invest in and implement new technology strategies for teaching and learning. However, business school deans can no longer ignore the potentially disruptive innovations that will occur in teaching and learning processes.